Walls composed of different materials: a brief review on thermal comfort - Antonelli, Jeferson Fernando Corrêa; Erba, Leandro Augusto; Azambuja, Maximiliano dos Anjos (National Journal of City Management, 2020)
The present work is dedicated to identifying the central researches related to the influence of the different materials that make up the walls in the performance of thermal comfort. At first, the keywords “Wall materials” and “Thermal comfort” were used in the search for scientific articles through a systematic review in the Scopus and Web of Science databases, restricted to the areas of Architecture and Urbanism, Social Sciences, Arts and Humanities. 85 scientific articles were identified, of which 44 were included in the research, the excluded did not have adherence, because they were out of the subject or in duplicate. In order to organize the data and discuss the subjects, four contexts were identified: building evaluation (39%), computer simulation (39%), prototype construction (15%) and laboratory experiment evaluation (7%). Among the materials, hemp and straw bales stood out by demonstrating the ability to cushion temperature variations in both winter and summer, and are therefore good thermal regulators. The melting temperature of the Phase-Change Material (PCM) of 25 ° C optimized the installation in all locations. The ceramic brick wall had a worse performance, from 1.25 to 1.45W / (m.K) in relation to the traditional mud walls at 1.1 to 1.2W / (m.K) and the earth block construction technique stabilized with cement at 1.05 to 1.25W / (m.K). The application of materials provided for wall construction is one of the best alternatives to achieve the condition of internal thermal comfort of buildings.